Pengaruh sarapan sehat terhadap semangat belajar anak usia Di sekolah SD Inpres Fatufeto 2 Kota Kupang: PENGARUH SARAPAN SEHAT TERHADAP SEMANGAT BELAJAR ANAK USIA DI SEKOLAH SDI FATUFETO 2 KOTA KUPANG - Setu, Yohana Teodosia (STIKES ADVAITA MEDIKA TABANAN, 2025)
ABSTRACT Background: Consuming food in the morning is an important activity to do before filling other activities every day, which serves to make it easier for individuals to think, learn, and perform activities optimally after waking up in the morning. Objective: the purpose of this research is to determine the Effect of Healthy Breakfast on the Learning Spirit of School-Age Children. Method: This study uses the design of this study is a survey design with a quantitative method. The sampling technique used was simple random sampling and the number of samples was 100 respondents. The variables in this study are health counseling and the level of knowledge of students about healthy breakfast for school children. The instrument used is a questionnaire given before and after counseling. Results: The results of the descriptive statistical analysis of the percentage proportion showed that healthy breakfast had a significant influence on learning enthusiasm (p <0.05), with a positive regression coefficient of 0.45. This shows that every improvement in breakfast quality is followed by an increase in learning enthusiasm by 45%. The results of the regression test were used to determine the relationship between the variables studied. Conclusion: There is a significant influence of providing healthy breakfast for school-age children on children's enthusiasm for learning at school. Keywords : Healthy breakfast, School-age children, Spirit of learning